Geriatric Suicide : A Brief Clinical Review - Avinash De Sousa (Indian Journal of Gerontology, 2009)
Geriatric suicide is on the rise worldwide. The present paper reviews the current literature on the risk factors of suicide in the elderly that may be detected through clinically routine practice. Medical illness, loneliness, physical disability and caregiver burden along with financial strain are some of the factors that may lead to elderly suicide. Divorce and widowhood are other important indicators. Management and preventive strategies including social management, outreach programs and other issues are discussed.